Managers’ Role in Systematic Risk: A Rejoinder to Chatterjee, Lubatkin, and Schulze (1999) - Baigent, Glenn; Nemiroff, Howard; Porrini, Patrizia (Journal of Comparative International Management, 2006)
We revisit the role of the manager as implied by the capital asset pricing model (CAPM) and address the three-decade discourse that has emerged in the Academy of Management Review concerning the responsibility of the manager. This discourse has embraced the conclusion that because CAPM only prices systematic risk and does not price unsystematic (firm-specific) risk, managers’ decisions and actions are not priced by CAPM. The management literature implies that because managers’ actions are not priced by CAPM, finance theory considers managers’ actions irrelevant. We demonstrate analytically that CAPM, and specifically systematic risk, does consider and price the role of the manager.